Effect of different disinfectants on the microhardness and roughness of acrylic resins for ocular prosthesis - Moreno, Amália [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Haddad, Marcela F. [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Bannwart, Lisiane C. [UNESP] (Wiley, 2013)
Background: Ocular prosthesis materials should have specific properties for their indication and durability; therefore, it is important to investigate their physical behaviour when affected by several disinfectants. Objectives: This study evaluated the influence of different disinfecting solutions on the microhardness and surface roughness of acrylic resins for ocular prosthesis. Materials and Methods: Fifty samples simulating ocular prostheses were fabricated with N1 resin and colourless resin and divided (n = 10) according to the disinfectant used: neutral soap, Opti-free, Efferdent, 1% hypochlorite (HYC) and 4% chlorhexidine (CHX). Samples were stored in saline solution at 37°C and disinfected during 120 days. Both microhardness and roughness were investigated before, after 60 days and 120 days of disinfection and storage. Microhardness was measured using a microhardner and the roughness with a roughness device. Results: N1 resin showed lower microhardness when compared with colourless resin (p < 0.05). HYC and CHX groups exhibited the highest change of microhardness and roughness values (p < 0.05). An increase in roughness and reduction in microhardness of ocular acrylic resins were observed after both periods of disinfection and storage (p < 0.05). Conclusion: Both disinfection/storage periods affected the microhardness and roughness values of the samples. © 2012 The Gerodontology Society and John Wiley & Sons A/S.
Keywords: acrylic resins; artificial eye; disinfection; maxillofacial prosthesis; physical properties